Diversity and Phosphate-Solubilizing Potential of Rhizosphere Bacteria Associated with Foxtail Millet (Setaria italica L.) - Samrawati Samrawati; Nurmuliayanti Muis; Sainab Sainab (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2025)
Foxtail millet (Setaria italica L.) is a cereal crop that can adapt to marginal environments; however, its growth is often limited by low phosphorus availability in the soil. Phosphate-solubilizing bacteria (PSB) in the rhizosphere play an important role in increasing phosphorus availability and promoting plant growth. This study aimed to isolate and screen phosphate-solubilizing bacteria associated with the rhizosphere of foxtail millet and evaluate their potential as plant growth-promoting rhizobacteria. Soil samples were collected from the rhizosphere and subjected to serial dilution followed by bacterial isolation on Nutrient Agar medium. Screening of phosphate-solubilizing activity was conducted using Pikovskaya medium by observing the formation of clear zones around bacterial colonies and calculating the solubilization index. Morphological characterization and Gram staining were also performed. The results showed that several isolates were capable of solubilizing phosphate with moderate solubilization indices. The colonies generally exhibited circular shapes, entire to undulate margins, convex elevation, and milky white coloration. Gram staining indicated the presence of both Gram-positive and Gram-negative bacteria. These findings suggest that rhizosphere bacteria associated with foxtail millet have potential as plant growth-promoting rhizobacteria.